(untitled) (Research, Society and Development, 2020)
Organizations can be understood as being social networks, formed by interactions and relationships between people and groups, configured in different ways, especially by mediating the roles that each actor develops and how it is structured. Thus, the present study proposes to verify the quality of the negotiations established in the network of interactions between the Federal Institute Farroupilha (IFFar) - campus Santo Augusto and the partners in their municipal context. To answer the challenge, the research follows the paths of the quantitative approach. Initially, it identifies the main organizational partners, then uses a questionnaire to complement the information obtained by the interviewees, who were the directors of each administrative area of IFFar - campus Santo Augusto and of each institution and organization and partner. As for whether this institution meets the expectations of its partners in the negotiations, the Servqual tool was used. As a result, six organizations were identified as being the main partners of the Institute and later a theoretical model was applied that represents this relationship network. With regard to meeting the expectations in the negotiations, among the five dimensions that make up the Servqual tool, four had a negative result.